Reaction of US and Chinese Stock Markets to COVID-19 News - Hock-Ann Lee; Venus Khim-Sen Liew; Mohd Fahmi Ghazali; Samina Riaz (Molecular Diversity Preservation International (MDPI), 2023)
The COVID-19 outbreak slowed down global economic activities substantially, resulting in unrest in the financial markets, especially in the beginning of the pandemic outbreak. This study aims to investigate if COVID-19 caused abnormal returns in the US and the Chinese stock markets in the beginning of the pandemic outbreak. Event study methodology is adopted for this purpose. This study finds that a significant negative impact appeared immediately after the Wuhan lockdown in the Chinese markets, while the US markets were slow to pick up. The former was more severely hurt after lockdown, while the latter was more brutally affected after COVID-19 was labeled a global threat. COVID-19 also played a significant role in connecting these two stock markets. The US and China should collaborate further in combating this novel and notorious global pandemic.